Artificial intelligence (AI) - Ismail, Fadillah; al Hosaini, Adnan Ali Hassan; Wei, Chan Shiau; Ruslan, Rumaizah; Maulad Bahrol, Khadijah (Penerbit Uthm, 2019)
“Artificial intelligence” is a synthetic term which – due to its suggestive potential – has caused many misunderstandings and false expectations. Its origin can be traced back to the year 1956. This year was important in many aspects. For example, the book “Automata Studies” came out, compiling now famous articles in the field of cybernetics (Shannon & McCarthy, 1956). Since the first appearance of the words “artificial intelligence”, usually associated with John McCarthy’s 1956 Dartmouth Summer Research Project, interest in the topic and research into the development of intelligent machines has seen several ups and downs.